2021
DOI: 10.1186/s40538-021-00210-1
|View full text |Cite
|
Sign up to set email alerts
|

Hydrochar from sugarcane industry by-products: assessment of its potential use as a soil conditioner by germination and growth of maize

Abstract: Background Hydrothermal carbonization (HTC) is a thermochemical process to convert biomass in carbon-rich materials (hydrochar). The use of sugarcane industry by-products in HTC has been evaluated, generating a hydrochar rich in nutrients, which could be used as a soil conditioner. We raised the hypothesis that the application of hydrochar in soil can improve its nutrient characteristics, bringing a better environment and favouring plant growth, expecting a development similar to that one obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 79 publications
0
7
0
Order By: Relevance
“…In another study, Yang et al 129 stated that kaolinite composite with walnut shell derived biochar improved its surface and adsorptive characteristics and nutrient release capacity, which ultimately positively impacted plant growth. Fregolente et al 130 found positive impact of hydrochar application on root and shoot development and dry biomass production of maize. Therefore, the parameters of seed germination and seedling growth revealed positive impacts of the synthesized materials with varying proportions.…”
Section: Resultsmentioning
confidence: 99%
“…In another study, Yang et al 129 stated that kaolinite composite with walnut shell derived biochar improved its surface and adsorptive characteristics and nutrient release capacity, which ultimately positively impacted plant growth. Fregolente et al 130 found positive impact of hydrochar application on root and shoot development and dry biomass production of maize. Therefore, the parameters of seed germination and seedling growth revealed positive impacts of the synthesized materials with varying proportions.…”
Section: Resultsmentioning
confidence: 99%
“…HSs are known to plant growth hormones like indole acetic acid and gibberellins, boosting root elongation and nutrient adsorption (Yang et al, 2021). However, high concentrations of AHA can introduce phytotoxic compounds, affecting seedling and root growth (Fregolente et al, 2021). Despite not detecting catechol, phenol, or cresol, other phytotoxic elements might have influenced the results.…”
Section: Plant Growth Phytotoxicity Testsmentioning
confidence: 99%
“…In Raza et al [136], the authors demonstrate that the integrated use of various amendments, including vinasse, with chemical fertilization, improves soil properties and rice yield. The hydrothermal carbonization process using vinasse and sugarcane bagasse allows producing hydrocarbon [137].…”
Section: Scope Of Studiesmentioning
confidence: 99%
“…Sector Industrial Application [56,58,66,[73][74][75]77,79,92,97,101,103,107,117,[135][136][137]144] Agriculture Soil remediation, crop improver (e.g., corn, tomato, rice), fertigation in sugar cane, fertilizer, among others [31,33,35,37,[39][40][41][42][43][44][45]48,49,52,55,59,62,63,69,71,72,76,81,82,[84][85][86]90,91,94,96,98,99,…”
Section: Studymentioning
confidence: 99%
See 1 more Smart Citation